Use of botulinum toxin in the treatment of temporomandibular disorders: integrative review (Research, Society and Development, 2020)
Introduction: Temporomandibular disorders (TMDs) have shown an increasing incidence in the population, causing pain and restricting the functions of the stomatognathic system, with that, the botulinum toxin has been gaining space in the dental field and is being used in the treatment of these disorders. Objective: to evaluate the effectiveness of the treatment of TMDs with botulinum toxin, systematizing the scientific evidence on the use of this therapy. Methodology: a search was carried out in the databases: Scientific Electronic Library Online (SCIELO) and US National Library of Medicine (Pubmed), with the descriptors: "Botulinum toxin", "Temporomandibular Disorder" and "Dentistry". The research took place online, and includes original articles in Portuguese and English addressing the proposed theme, published between 2010 and 2020, the exclusion criteria followed by articles in duplicate and that did not include the object of study, as well as theses, dissertations, monographs, books and book chapters. Results: 10 articles were analyzed, in which they reported that the botulinum toxin plays a role in reducing the release of inflammatory mediators that cause pain, becoming effective, without systemic or permanent side effects. Conclusion: Botulinum toxin as a therapeutic method has been shown to be effective in the treatment of TMDs, however, there is a need for further studies in the area.